Negatively Charged Nanosheets Significantly Enhance the Energy‐Storage Capability of Polymer‐Based Nanocomposites. Issue 25 (13th May 2020) - Bao, Zhiwei; Hou, Chuangming; Shen, Zhonghui; Sun, Haoyang; Zhang, Genqiang; Luo, Zhen; Dai, Zhizhan; Wang, Chengming; Chen, Xiaowei; Li, Liangbin; Yin, Yuewei; Shen, Yang; et al.
Abstract: Polymer‐based dielectric materials play a key role in advanced electronic devices and electric power systems. Although extensive research has been devoted to improve their energy‐storage performances, it is a great challenge to increase the breakdown strength of polymer nanocomposites in terms of achieving high energy density and good reliability under high voltages. Here, a general strategy is proposed to significantly improve their breakdown strength and energy storage by adding negatively charged Ca2 Nb3 O10 nanosheets. A dramatically enhanced breakdown strength (792 MV m −1 ) and the highest energy density (36.2 J cm −3 ) among all flexible polymer‐based dielectrics are observed in poly(vinylidene fluoride)‐based nanocomposite capacitors. The strategy generalizability is verified by the similar substantial enhancements of breakdown strength and energy density in polystyrene‐based nanocomposites. Phase‐field simulations demonstrate that the further enhanced breakdown strength is ascribed to the local electric field, produced by the negatively charged Ca2 Nb3 O10 nanosheets sandwiched with the positively charged polyethyleneimine, which suppresses the secondary impact‐ionized electrons and blocks the breakdown path in nanocomposites. The results demonstrate a new horizon of high‐energy‐density flexible capacitors. Abstract : A general strategy is developed to enhance energy storage of nanocomposites. Through inserting negatively charged Ca2 Nb3 O10 nanosheets into a polymer matrix, a reversed local electric field is generated and further blocks the breakdown path. A record‐high energy storage of 36.2 J cm −3 is achieved in poly(vinylidene fluoride). The strategy is also utilized in polystyrene‐based nanocomposites and is verified by phase‐field simulations.